How do price distortions of fossil energy sources affect China's green economic efficiency?. (1st October 2021) - Sha, Ru; Li, Jinye; Ge, Tao
Abstract: Improving green economic efficiency (GEE) contributes to the sustainable development of China's economy. The market-oriented reform of fossil energy prices is yet incomplete, resulting in distortions which have significant implications for China's GEE. This study measures different types of fossil energy price distortions and GEE based on panel data, and also analyzes how these fossil energy price distortions affect GEE using the System-GMM model. Additionally, potential influencing mechanisms are explored. The main results show that (1) all fossil energy prices are distorted, with coal and oil having larger distortions. Additionally, regional energy price distortions are characterized as low in eastern China and high in the central and western regions. (2) Fossil energy price distortions exhibit significant negative impacts on GEE from a national perspective. The sub-group analysis also shows negative effects on GEE but different regions have heterogeneous impacts. (3) Mechanism analysis illustrates that negative fossil energy price distortions further hinder GEE by inhibiting technological innovation and impeding the optimization of the energy consumption structure. It is necessary to improve market-based energy pricing mechanism and develop differentiated regional energy pricing policies for the realization of China's green economy. Highlights: Different types of fossil energy price distortions are measured. Green economic efficiency (GEE) of provinces in China is calculated. Energy price distortions negatively affect GEE at both national and regional levels. Fossil energy price distortions exhibit heterogeneous effects on regional GEE. The influencing mechanisms of energy price distortions are further explored.